MARINE BIODIVERSITY OF INDONESIA: LARVAL FISH PERSPECTIVE - Syahailatua, A. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2006)
Marine life of Indonesia is very well known as a high diversity according to Ekman's hyphothesis. However, from the larva fish perspectives, this hypothesis seems to be rejected according to the comparative results of larval fish studies during the Snellius Expedition (1984-1985) in Banda Sea and the larval fish observation related to the East Australian Current (1998-1999) off New South Wales coast in Australian waters. Larval fish diversity from some previous studies over the world is also included. Several suggestions are also recommended to enhance our knowledge in marine biodiversity including improvement in marine biodiversity observation such as, research programs, field and laboratory facilities and numbers of taxonomists, and also collaborative works among research institutes, universities, and non-governmental organizations.